Mercury Kushta Induced Histopathological Changes in Kidneys of Wister Rats - Sakina Jamil, Raees Abbas Lail, Zunaira Qayyum, Hadia Rana, Jahangir Anjum, Sara Akram (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To see the histological changes of Kushta which contains mercury, on kidneys of wister rats Material and Methods: A total of 42 Wistar rats were used in this animal experiment, which was separated into five exposure groups and one control group. The kidneys of rats were morphologically altered by the use of both indigenous and prescription mercury preparations. Results: Morphological changes in kidneys of exposed rats included multi-focal and diffuse glomerulonephritis, mesangial widening, increase in glomerular cellularity, thickening of capillary walls and glomerular basement membrane, tubular necrosis, tubular dilatation, tubular vacuolisation, proteineous casts in tubules and mononuclear interstitial inflammation were seen at the end of 8 weeks. Conclusions: In wister rats, an indigenous mercury herbo-mineral preparation (Kushta) causes harmful morphological changes in the liver.